Descriptive study about nutritious habits on breakfast and lunch of Viladecans (Barcelona) adolescents - Mª Adela Amat Huerta; Vanesa Anuncibay Sánchez; Juana Soto Volante; Nuria Alonso Nicolás; Ana Villalmanzo Francisco; Sonia Lopera Ramírez (Fundación para el Desarrollo de la Enfermería, 2006)
Feeding during childhood and preadolescence has a great importance on the adult projection quality of life. Breakfast is all a food, very necessary for the physical and intellectual development of children, but it is the ingestion that is most omitted. It has much more importance of what we give him. Objectives: To know the nourishing habits in breakfast and lunch in the preadolescence. Design: An observational, descriptive study was chosen, with a study sample of 270 scholars aged between 9 and 13.Results: We could observe that 73% of the study participants have breakfast every day and 4,1% of them never have breakfast. Among these that never have breakfast, there are more girls (5'4%). The reason for not having breakfast is the lack of time (48.2%), and for not having lunch the lack of hunger (24.1%). The most frequent foods on breakfast are milk (82,2%) and cocoa (54,8%), and sandwiches on lunch. Conclusions: Girls represent the group that less have breakfast every day. There are few of them who follow the basic triad: milk, cereal, and fruit.